PENGARUH KEPEMILIKAN ASING, DIVERSITAS DEWAN KOMISARIS DAN DIREKSI SERTA FOREIGN OPERATION TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Pertambangan Terdaftar di BEI Periode 2018-2022) - -, Masroina - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to examine the influence of foreign ownership, diversity of the board of commissioners and directors and foreign operations on tax avoidance in Mining Companies listed on the IDX for the 2018-2022 period. This type of research is quantitative. The population in this research is all Mining Sector Companies listed on the Indonesia Stock Exchange in the 2018-2022 period with the criteria 1) Mining companies listed on the Indonesia Stock Exchange during 2018-2022; 2) Companies that experienced profits during the observation period, namely 2018-2022; 3) Companies that have subsidiaries (subsidiaries) or branches abroad or operational activities abroad. 4) Companies that use the Rupiah currency unit (Rp) in their financial reports; and obtained a sample of 23 companies with an observation period of 5 years. The data analysis method used is multiple linear regression. The research results found that foreign ownership, diversity of the board of commissioners and directors and foreign operations had a positive and significant effect on tax avoidance in mining companies listed on the IDX for the 2018-2022 period. Keywords: Foreign Ownership, Diversity of the Board of Commissioners and Directors, Foreign Operations, Tax Avoidance, Mining Compani